Efficacy of sulphur on growth, yield and bulb quality in onion (Allium cepa L.) - Dash, P Tripathy, B B Sahoo, D Patel, D K (Journal of Spices and Aromatic Crops, 2016)
Sulphur has been recognised as an important nutrient for higher yield and quality of onion (Allium cepa L.) bulbs. Field experiment was conducted during rabi, 2010–11 to 2012–13 to study the efficacy of sulphur nutrition in onion. The treatment combination consisted of two sources of sulphur (gypsum and elemental sulphur) and four levels of sulphur (0, 15, 30 and 45 kg ha-1) in Factorial RBD with three replications. The pooled results over three years revealed significantly higher efficacy of gypsum over elemental sulphur for polar diameter (3.13 cm), bulb weight (48.37 g) and marketable bulb yield (101.39 q ha-1). Similarly, irrespective of sources, sulphur @ 30 kg ha-1 recorded significantly higher plant height (55.78 cm), number of leaves plant-1 (11.08), bulb weight (67.34 g), bulb yield (marketable, 160.71 q ha-1 and total, 224.52 q ha-1) and TSS (12.03%) with higher BC ratio (1.47) as well as better shelf life. Application of sulphur @ 30 kg ha-1 as gypsum may be recommended in onion crop for obtaining higher bulb yield with higher BC ratio and better keeping quality.